2020
DOI: 10.3390/antibiotics9060324
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multi-Resistant Microorganisms and Antibiotic Stewardship among Hospitalized Patients Living in Residential Care Homes in Spain: A Cross-Sectional Study

Abstract: Antimicrobial resistance is a growing global health problem. Patients living in care homes are a vulnerable high-risk population colonized by multidrug-resistant organisms (MDRO). We identified a case series of 116 residents of care homes from a cohort of 540 consecutive patients admitted to the internal medicine service of our hospital. We performed early diagnostic tests of MDRO through anal exudates in our sample. The prevalence of MDRO colonization was 34.5% of residents and 70% of them had not been previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…It was also very close to the reports from India (66.12%) [87] and Egypt (65.5%) [88,89]. In contrast to our finding in Ethiopia, a lower prevalence of MDR has been reported from Germany (60%) [90], Nepal (42.6%) [91], Australia (36%) [92], Indonesia (28.7%) [93], the USA (27%) [94], Spain (34.5%) [95] and France (11.6%) [96]. Several factors may play a role in the difference including the magnitude and style of antimicrobial use and infection prevention practices.…”
Section: Plos Onesupporting
confidence: 88%
“…It was also very close to the reports from India (66.12%) [87] and Egypt (65.5%) [88,89]. In contrast to our finding in Ethiopia, a lower prevalence of MDR has been reported from Germany (60%) [90], Nepal (42.6%) [91], Australia (36%) [92], Indonesia (28.7%) [93], the USA (27%) [94], Spain (34.5%) [95] and France (11.6%) [96]. Several factors may play a role in the difference including the magnitude and style of antimicrobial use and infection prevention practices.…”
Section: Plos Onesupporting
confidence: 88%
“…This evidence suggests, on the one hand, that the WAAW does not contribute much to an increase in awareness of AMR and, on the other hand, that the COVID-19 pandemic may have had a negative impact. Thus, the COVID-19 pandemic could have contributed to reducing the information available, measures implemented, research conducted, and general interest in future pandemics in terms of the multi-drug-resistant infections, which are already plaguing several Mediterranean countries [25,26,[31][32][33][34]. For these reasons, there is a need for novel strategies to increase the interest of the general public and healthcare professionals, especially in countries where AMR rates are high.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study by our research group, we identified elderly patients living in residential care homes as a particularly vulnerable population for colonization by OXA-48 CRE [ 76 ]. Specifically, 34.5% of these patients showed positive rectal colonization by multiresistant bacteria, 27.5% of them by OXA-48-producing K. pneumoniae and 2.5% by OXA-48-producing E. coli .…”
Section: Oxa-48 Cre Outbreaks In Spainmentioning
confidence: 99%